Tactile and olfactory stimulation reduce anxiety and enhance autonomic balance: a multisensory approach for healthcare settings - Junfang Xie; Mohamed Elsadek; Zhang Deshun; Zhiyi Zhou; Jie Gao (BMC Psychology)
Abstract Anxiety in healthcare environments—particularly in dental clinics—presents a significant challenge, often impairing patient cooperation and clinical outcomes. This study investigated the effectiveness of multisensory engagement—combining visual, tactile, and olfactory stimuli—in reducing anxiety and promoting physiological relaxation within a dental clinic setting. A within-subject experimental design was employed, exposing 40 participants to five conditions: control (no sensory input), visual (plant observation), tactile (plant interaction), olfactory (plant scent), and combined tactile-olfactory stimulation. Anxiety was assessed using the State-Trait Anxiety Inventory– State (STAI–S), and physiological responses were measured via heart rate (HR), heart rate variability (HRV) indices (LF/HF ratio, RMSSD, SDNN), and skin conductance (SC). Findings revealed significant reductions in anxiety and stress markers across all sensory conditions compared to the control. The tactile-olfactory combination elicited the most consistent improvements across physiological indices, including a 42.3% reduction in STAI–S scores, a 66.0% decrease in the LF/HF ratio, 81.6% increase in RMSSD (olfactory condition peak), a 54.7% increase in SDNN, a 15.9% decrease in HR, and a 67.2% reduction in SC. These findings underscore the potential of nature-based multisensory interventions to enhance autonomic regulation and psychological well-being in clinical environments. The study offers novel insights into the application of biophilic design principles in healthcare, demonstrating that engaging multiple sensory pathways, especially combined tactile and olfactory inputs, can help mitigate patient anxiety and promote relaxation.